ChemInform Abstract: Thermodynamic Assessment of the Ga—X (X: B, Ca, Sr, Ba) Systems Supported by First‐Principles Calculations. Issue 14 (March 2016) - Li, Xi; Cheng, Kaiming; Yuan, Xiaoming; Zhao, Dongdong; Xin, Jinghua; Wang, Weiwei; Zhang, Cong; Du, Yong
Abstract: Review: 56 refs.